Applications of Artificial Intelligence: Business Management Perspective - Arshi Naim (Research Parks Publishers, 2022)
This is a short paper based on qualitative for the benefits of Artificial Intelligence (AI) which is the most growing branch of computer science and most of the service sectors are obtaining benefits from its application. This is an extended research article provides a general role of AI in financial services and its definition in practical scenarios. The research work is mostly qualitative and does not include any data analysis for its results. This article describes the major benefits derived by the practices of AI in general in the banking and financing firms. For the study, some examples of the role of AI in financial firms are analyzed and results are given from the positive observation shared by the FI firms on their official website. AI benefits both service providers and users, this research report explains the advantages of AI in finance and also describes how AI can aid in market development.